Congenital hairy polyp and autoamputation in an infant with acute otitis media - İnce, Damla and Turan, Özden and Gemici, Hatice Betül and Erdoğan, Şenay and Çakır, Çağlar (The Turkish Journal of Pediatrics, 2014)
Hairy polyp is a rare, benign tumor that frequently localizes in the nasopharynx and oropharynx. The embryogenesis of hairy polyp is not known precisely. The clinical profile can vary depending on the size and location of the tumor. In this report, we present a case with hairy polyp who was admitted with acute otitis media and completely recovered after spontaneous autoamputation.